Analisis Representasi Islam Moderat dalam Konten Dakwah Digital : Studi Kasus YouTube @NussaOfficial - Ludia Amanda Pratiwi; Ayu Dara Kinanti; Adhi Kusuma (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of digital technology has changed the way religious values are broadcast, including in the context of preaching. Platforms such as YouTube have become a new space for preachers to convey religious messages to the wider community. One channel that has attracted public attention is @NussaOfficial. This channel carries a moderate preaching approach with a modern and creative presentation style. This study aims to analyze the representation of moderate Islam in digital preaching content on the @NussaOfficial YouTube channel using the perspective of Stuart Hall's discourse theory. The critical discourse analysis method is used to understand how meanings are formed and represented through word choice, narratives, and visualizations. The results of the study show that NussaOfficial has succeeded in representing Islam as a religion that is peaceful, tolerant, inclusive, and relevant to modern life, while also forming a moderate Islamic identity amidst the flow of digital information.